Residents' Dissatisfaction and All-Cause Mortality. Evidence from 74 European Cities - Ribeiro, Ana I.; Fraga, Sílvia; Barros, Henrique (Frontiers in Psychology, 2018)
Background: About two thirds of the Europeans reside in cities. Thus, we must expand our knowledge on how city characteristics affect health and well-being. Perceptions about cities’ resources and functioning might be related with health, as they capture subjective experiences of the residents. We characterized the health status of 74 European cities, using all-cause mortality as indicator, and investigated the association of mortality with residents’ dissatisfaction with key domains of urban living. Methods: We considered 74 European cities from 29 countries. Aggregated data on residents’ dissatisfaction was obtained from the Flash Eurobarometer, Quality of life in European cities (2004-2015). For each city a global dissatisfaction score and a dissatisfaction score by domain (environment, social, economic, healthcare and infrastructures/services) were calculated. Data on mortality and population was obtained from the Eurostat. Standardized Mortality Ratios, SMR, and 95% Confidence Intervals (95%CI) were calculated. The association between dissatisfaction scores and SMR was estimated using Generalized Linear Models. Results: SMR varied markedly (range 73.2-146.5), being highest in Eastern Europe and lowest in the South and Western European cities. Residents’ dissatisfaction levels also varied greatly. We found a significant association between city SMR and residents’ dissatisfaction with healthcare (β=0.334; IC95% 0.030, 0.639) and social environment (β=0.239; IC95% 0.015, 0.464). No significant association was found with the dissatisfaction scores related with the physical and economic environment and the infrastructures/services. Conclusions: We found a significant association between city levels of mortality and residents’ dissatisfaction with certain urban features, suggesting subjective assessments can be also used to comprehend urban health.